2022
DOI: 10.1007/978-3-031-11454-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Targeted DNA Methylation: Towards Long-Lasting Reprogramming of Gene Expression?

Abstract: DNA methylation is an essential epigenetic mark, strongly associated with gene expression regulation. Aberrant DNA methylation patterns underlie various diseases and efforts to intervene with DNA methylation signatures are of great clinical interest. Technological developments to target writers or erasers of DNA methylation to specific genomic loci by epigenetic editing resulted in successful gene expression modulation, also in in vivo models.Application of epigenetic editing in human health could have a huge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 102 publications
(185 reference statements)
1
4
0
Order By: Relevance
“…Consistently, acquisition of histone methylation alone is not enough for stably silencing the transcriptional expression of UCHL1, as also reported for, e.g., HER2, for which persistent silencing required both a DNA methyltransferase and EZH2 [ 46 , 51 ]. Although not in H1299 cells, cotargeting of dCas-MSssI (Q147L) and dCas-SKD did result in prolonged downregulation of UCHL1 in HEK293T cells, confirming other reports [ 17 , 27 , 29 ]. Straightforward long-term reprogramming of gene expression by epigenetic editing would provide a powerful and flexible approach to study the role of any given gene in various contexts.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistently, acquisition of histone methylation alone is not enough for stably silencing the transcriptional expression of UCHL1, as also reported for, e.g., HER2, for which persistent silencing required both a DNA methyltransferase and EZH2 [ 46 , 51 ]. Although not in H1299 cells, cotargeting of dCas-MSssI (Q147L) and dCas-SKD did result in prolonged downregulation of UCHL1 in HEK293T cells, confirming other reports [ 17 , 27 , 29 ]. Straightforward long-term reprogramming of gene expression by epigenetic editing would provide a powerful and flexible approach to study the role of any given gene in various contexts.…”
Section: Discussionsupporting
confidence: 88%
“…We explored the possible role of UCHL1 in smoking-related lung diseases via chemical inhibitor treatment and conventional plasmid-based upregulation in cell lines. Furthermore, CRISPR/dCas9-mediated epigenetic editing of UCHL1 (using a catalytically inactivated Cas9) [ 17 ] – was employed to up- and downregulate the expression of UCHL1 to further validate these findings.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, DNA-targeted approaches are currently explored to remove mutated mitochondrial DNA from diseased cells ( 68 ). To modulate DNA methylation, DNMT and TET enzymes can be targeted to loci of interest already reaching mainstream applications for nuclear DNA ( 69 ). Since DNA (de)methylating enzymes also localize to mitochondria ( 70 ), these approaches might turn out effective in treating mitochondrial dysfunction for a range of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is found to be strongly associated with gene expression regulation and therefore in the development of different pathologies ( 52 ). In the current study, the mechanism of elevated PLEKHA4 expression in LGG was investigated, and results showed that PLEKHA4 overexpression was negatively correlated with the methylation of cg06339706, cg01093065, cg06705122 and cg23002721, which were located in the promotor or near the TSS of PLEKHA4 gene.…”
Section: Discussionmentioning
confidence: 99%